KESTABILAN SISTEM KONTROL JARINGAN TERHADAP WAKTU TUNDA - br. Ginting, Juliana; widowati, widowati (MATEMATIKA, 2010)
. In this paper, we proposed the stability analysis of networked control system with time delay. Delay in a network is something that can not be avoided when transmitted digital data over control devices. Network control system is discussed here consists of clock driven sensor, event driven controller, actuator, and plant. In the network control system usually contains delays and sampling period with effect the system stability. Stability region in a network control system can be represented through the relationship between Maximum Allowable Transfer Interval and sampling period.